PENGARUH LATIHAN LISAN TERHADAP TINGKAT KREATIVITAS BELAJAR BAHASA ARAB SISWA - Abdullah Asyiq (Muróbbî: Jurnal Ilmu Pendidikan, 2020)
In learning Arabic, the practice of pronunciation in Arabic is a very important language skills exercise. Because if a word is not pronounced according to it should be able to change the meaning. Language is also a communication tool that can convey thoughts and feelings, the use of language to express thoughts and feelings verbally concerning various aspects that not only involve a series of sounds, tones, and rhythms of true intonation but also concerning the choice of words (diction) and sentences correct and appropriate in accordance with the situation in which the expression of verbal expression can be achieved properly through oral exercises with or without recorded material, so that the influence of the method undertaken by a teacher, especially oral exercises on the development of learners in learning creativity, because Arabic subject is a subject that is directed to encourage, guide, develop and foster abilities and foster a positive attitude towards Arabic, both receptive, namely the ability to understand other people's speech and understand reading. Productive ability is the ability to use language as a communication tool both verbally and in writing.